2022
DOI: 10.1111/wrr.12995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activity as an adjunct treatment on healing outcomes and recurrence of venous leg ulcers: A scoping review

Abstract: Healing time is protracted and ulcer recurrence is common in patients with venous leg ulcers. Although compression is the mainstay treatment, many patients do not heal timely. Physical activity may be a clinically effective adjunct treatment to compression to improve healing outcomes. This scoping review provides a broad overview of the effect of physical activity as an adjunct treatment to compression on wound healing and recurrence. We followed the six‐step framework developed by Arksey and O'Malley. We sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 82 publications
(367 reference statements)
1
7
0
1
Order By: Relevance
“…Our data suggested higher levels of PA were positively correlated with better QoL. This is consistent with prior research examining factors that influence PA levels in people with VLUs, where a strong positive correlation between PA levels and overall QoL in this patient population was also identified (10,21). Similarly, past clinical trials found that participants who undertook an exercise intervention had higher QoL scores than those who received standard compression treatment (22, 23).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data suggested higher levels of PA were positively correlated with better QoL. This is consistent with prior research examining factors that influence PA levels in people with VLUs, where a strong positive correlation between PA levels and overall QoL in this patient population was also identified (10,21). Similarly, past clinical trials found that participants who undertook an exercise intervention had higher QoL scores than those who received standard compression treatment (22, 23).…”
Section: Discussionsupporting
confidence: 90%
“…Physical activity (PA) may be an effective adjunct treatment to compression to improve ulcer healing and recurrence (9). A recent scoping review has found that multicomponent exercises targeting the lower extremity as an adjunct for compression therapy may improve calf muscle pump function, thereby enhancing circulation in the lower extremities and ultimately improving ulcer healing and preventing recurrence (10). There are also multiple barriers to PA and exercising in people with VLUs, including pain, psychological distress, and a lack of clear exercise instructions (11).…”
mentioning
confidence: 99%
“…Several types of physical activity, such as resistance exercise, walking, aerobic exercise, and ankle exercise, are suggested as adjunct therapies to compression therapy for managing VLU [ 5 , 51 , 52 ]. According to a recent analysis, resistance training is the physical activity/exercise intervention that has been studied the most and is clinically effective for reducing ulcer size and increasing calf muscle pump function in people with VLU [ 53 ]. The results of the study are supported by findings from earlier studies; indeed, a recent study demonstrated that the use of a supervised exercise program (a combination of resistance, aerobic, and flexibility training) in conjunction with compression therapy was feasible and acceptable in the treatment of venous ulcers [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise programs focused on calf muscle activities and ankle rehabilitation are the most effective at increasing the VLU healing rate. Some reports demonstrated that patients adhering to exercise programs, specifically resistance exercise combined with ankle and/or foot range-of-motion exercises, as an adjunctive treatment to standard care, have a higher chance of healing and better functional outcomes than those who do not adhere to exercise programs [98][99][100][101]. In addition, they are also more likely to avoid an ulcer recurrence [95].…”
Section: Lifestyle and Physical Exercisementioning
confidence: 99%